Early Experience With Single-Stage Transanal Endorectal Pull Through For Rectosigmoid Hirschsprung’s Disease - Shrestha, MK; Sherchan, M; Dhoubhadel, BK; Basnet, RB (Journal of Nepal Paediatric Society, 2015)
On 24th August 2015, the spelling of the third author's name was changed from Dhaubhadel TO Dhoubhadel - Editor. Introduction: Recent trends in surgery for Hirschsprung’s disease (HD) have been towards earlier operation and fewer surgical stages. A single-stage transanal endorectal pull through (TEPT) is the latest development and minimally invasive technique for HD. This observational prospective study was designed to evaluate the safety and efficacy of single-stage TEPT technique in the management of rectosigmoid HD. Materials and Methods: Infants and children with biopsy-proved aganglionosis and barium enema (BE) documented rectosigmoid HD were included for single stage TEPT. Twenty children aged 22 days to 7 years (17 boys and 3 girls) underwent one stage TEPT over 5 year period. Median follow up was 18 months (range 6-36 months). These patients were evaluated with regard to age, sex, intraoperative details, postoperative functional outcome and complications and need for secondary surgical procedure. Results: The operating time was 105-180 minutes (mean 120 minutes). The length of resected bowel was 18-30 cm (mean 25 cm). Intraoperative blood loss was 5-40 ml, less in infants compared to older children. Blood transfusion was needed in none out of 12 infants and 2 out of 8 older children. Transient perianal excoriation occurred in 16 patients. Postoperative enterocolitis occurred in one patient. One patient developed constipation with encopresis following anastomotic stricture. None had adhesive obstruction and prolapse of pulled through colon, one required colostomy for anastomotic leakage and peritonitis while another had retained aganglionic segment and re-do pull through was required. Conclusion: Single-stage TEPT can be performed successfully in all age of children. The technique is safe, easily learned and has good clinical results. DOI: http://dx.doi.org/10.3126/jnps.v34i3.11617 J Nepal Paediatr Soc 2014;34(3):188-194